2008
DOI: 10.1002/ppap.200800061
|View full text |Cite
|
Sign up to set email alerts
|

High‐Rate SiO2 Deposition by Oxygen Cold Arc Plasma Jet at Atmospheric Pressure

Abstract: SiO2 thin films were deposited by a cold arc plasma jet at atmospheric pressure. The cold arc plasma jet was operated with O2 gas of 30 L · min−1, while a He/TEOS mixture of 1 000 sccm was added to the plume of the plasma jet as a precursor. The plasma jet was continuously moved in the xy direction for uniform film thickness. The deposition rate at various conditions was studied by controlling the substrate distance, precursor inlet position, and substrate temperature; the physical and chemical properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In the experiment, Q source was decreased from 200 to 50 SCCM, while Q O2 was increased from 20 to 80 SCCM (O 2 /HMDSO ≈ 50), aiming at the complete oxidation of HMDSO molecules introduced into the plasma jet. In addition, to avoid the particulate contamination of the film surface, the distance d was shortened from 15 to 5 mm to expose the substrate surface to the plasma jet, and simultaneously, RF power was reduced from 200 to 150 W. In this condition, although the efficiency in transforming HMDSO into the film estimated roughly from the film volume was as low as approximately 1%, the deposition rate of approximately 13 nm/s was obtained, the value of which is still greater than those obtained in other PECVD methods using AP plasma (0.2-5 nm/s) [16,[21][22][23]. From Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the experiment, Q source was decreased from 200 to 50 SCCM, while Q O2 was increased from 20 to 80 SCCM (O 2 /HMDSO ≈ 50), aiming at the complete oxidation of HMDSO molecules introduced into the plasma jet. In addition, to avoid the particulate contamination of the film surface, the distance d was shortened from 15 to 5 mm to expose the substrate surface to the plasma jet, and simultaneously, RF power was reduced from 200 to 150 W. In this condition, although the efficiency in transforming HMDSO into the film estimated roughly from the film volume was as low as approximately 1%, the deposition rate of approximately 13 nm/s was obtained, the value of which is still greater than those obtained in other PECVD methods using AP plasma (0.2-5 nm/s) [16,[21][22][23]. From Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Several types of AP plasma sources, including dielectric barrier discharges, radio frequency glow discharges and AP plasma jets, have successfully been used to fabricate Si-related coatings [13][14][15][16][17][18][19][20][21][22][23][24]. In particular, AP plasma jet is a simple plasma source that is usable in open air conditions, the plasma of which can be generated with argon (Ar), and thus, it is one of the most promising techniques for Si-related coatings in a less expensive, more flexible and continuous manner of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 exhibits the smoothest PC substrate, with a surface roughness of R ms at 1.6 nm and R a at 1.3 nm and an optimal substrate distance of 3 cm, resulting from deposition of a 306.1 nm thick SiO x C y N z film at a deposition rate of 19.1 nm/s. Han et al [11] claimed high-rate SiO 2 deposition of TEOS plasma-polymerized SiO x onto silicon substrate by APPJ at a deposition rate of up to~270 nm/min (4.5 nm/s). In this study, fast deposition of SiO x C y N z films onto PC substrates at deposition rates of 19.1-19.9 nm/s is achieved by the injection of a TMDSO precursor into an air plasma jet at room temperature (~23°C) and atmospheric pressure.…”
Section: Surface Morphologymentioning
confidence: 99%
“…PECVD has thus become a promising technique for providing hard transparent protective coatings on transparent polymers, especially at atmospheric pressure, due to its economical (low cost, high processing speeds and simple system which does not use vacuum equipment) and ecological advantages [7]. Plasma polymerization, a special PECVD process with precursors such as tetraethoxysilane (TEOS) [8][9][10][11][12][13][14], hexamethyldisilazane (HMDSO) [15][16][17][18][19][20] and hexamethyldisilazane (HMDSN) [21,22], has been proven to synthesize organosilicon thin films onto hard silicon or glass substrates at atmospheric pressure. However, only a few studies have reported the deposition of organosilicon thin films onto soft polymer substrates, such as PC [7,23,24], polyethylene terephthalate (PET) [25][26][27] and polyethylene-2,6 naphlate (PEN) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Such processes are particularly promising to treat complex 3D objects by mounting the plasma source on a robot. Table 3 shows a list of works performed with millimetric jets and torches for PECVD at atmospheric pressure (Ref [76][77][78][79][80][81][82][83][84][85][86]. Historically, plasma micro-torches were proposed with thermal plasmas (Ref 87-89) rather than with nonequilibrium plasmas.…”
Section: Influence Of the Plasma Size On Depositionmentioning
confidence: 99%